PERBEDAAN TINGKAT KECUKUPAN ENERGI, PROTEIN DAN STATUS GIZI BALITA YANG DIASUH SENDIRI DENGAN BALITA YANG DITITIPKAN DI TAMANPENITIPAN ANAK DI KECAMATAN NGALIYAN KOTA SEMARANG - Yoga Adhi Dana; Dina Rahayuning Pangestuti; Laksmi Widajanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Toddler period is an important period in the growth of the child and requires a balanced nutrition. In districtNgaliyanhousing complex still found some children with malnutrition status.Daycare (TempatPenitipanAnak/TPA) in the District Ngaliyan Semarang, help worker parents who have toddlers to keeping the toddler in order to grow well. This study aimed to analyze the differences in the intake of energy, protein and nutritional status Toddlers in Daycare and without daycare in the District Ngaliyan Semarang. This type of research is an explanatory research using cross sectional approach. The population is all children aged 2-5 years. The number of subjects selected 46 children from 23 toddler in daycare and from 23 children without daycare by using purposive sampling technique. Data taken with measurements and observations collected by questionnaire, and then performed normality test using the Shapiro-Wilk test with significance values (p)> 0.05).The results showed no difference in the level of energy sufficiency, (p = 0.473),there was no difference in protein sufficiency level (p = 0.0762),there was no difference in the nutritional status based index BB / U (p = 0.761), with the index of BB / TB (p = 0073),and with the index of TB / U (p = 0194). ). Concluded there was no difference in the level of adequacy of energy, protein and nutritional status in Toddlers Daycare and Toddlers without Daycare